Tactical deception to hide sexual behaviour: macaques use distance, not visibility - Overduin-de Vries, A. M. (Behav Ecol Sociobiol, 2015)
Although tactical deception (TD) may be employed to hide sexual behaviour, there is as yet no firm evidence for it. Hiding may be guided by cognitive mechanisms consistent with either no, low or high level TD, such as exploiting male peripheral positions (no TD), creating distance (TD level 1) or hiding behind screens (TD level 1.5 which involves visual perspective taking (VPT)). Macaques are capable of VPT in a food context, suggesting that they may employ TD level 1.5. We investigated, in an observational study with temporarily provided hiding screens, which strategy was used to hide sexual behaviour in captive groups of two macaque species (Macaca mulatta and Macaca fascicularis). Sexual behaviour only sporadically took place near screens, and the few copulations near screens were not systematically hidden from the alpha male, precluding TD level 1.5. Instead, both females and non-alpha males were at a larger distance from the alpha male during sexual interactions than otherwise, consistent with TD level 1. Creating peripheral locations (TD level 1) may be effective in improving sexual opportunities in many species. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00265-015-1946-5) contains supplementary material, which is available to authorized users.